Comparison of Anura Species Diversity Organic and Inorganic Rice Fields in Nagari Sungai Buluh, Batang Anai District - katon agusdi; fitra nugraha (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Rice field ecosystem as a man-made wetland ecosystem provide suitable habitat for wildlife, especially amphibians and reptiles (herpetofauna). The existence of amphibians in rice fields is threatened due to the intensive use of chemicals that cause changes in species composition. The purpose of this study was to compare the diversity of anura in organic and inorganic rice fields. The research was conducted from October to December 2021 in organic and inorganic rice fields in the Padang Pariaman area using the plot method. The total species found were 2 types of anura from 1 family from both rice fields . The highest abundance value is in organic rice field habitat. Fejervarya cancrivora was the dominant type of anura at both locations.The highest diversity index was found in organic rice fields (H' = 0.6363).